Effect of Fertilizers on the Incidence of Anthracnose Disease, Yield and Quality of Mango - Chowdhury, MNA; Rahim, MA (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Effect of different fertilizers on the control of anthracnose disease, yield and quality of mango cv Amrapali was investigated. Application of combined fertilizers gave the highest fruit set, fruit retention and fresh fruits, therefore, produced the highest yield per plant and per hectare. The highest number of healthy fruits was found from 2nd year crop and the lowest was obtained from 1st year. The highest (8.47 t/ha) yield was obtained from 2nd year and the lowest (4.58 t/ha) was obtained from 1st year crop. Among the treatments, combined application of NPK, ZnSo4, Gypsum and Cowdung gave the highest (50.67) number of healthy fruits and the lowest (16) was obtained from untreated plant. The highest (12.41 t/ha) yield was obtained from combined application of NPK, ZnSo4, Gypsum and Cowdung and the lowest (3.88 t/ha) was obtained from untreated plant. In respect of combined effect, the highest (15.22 t/ha) yield was obtained from 2nd year x T9 treated plant and the lowest (2.95 t/ha) was found in untreated 1st year plant. Key words: Mango, fertilizers, anthracnose, yield. DOI = 10.3329/jard.v5i1.1461 J Agric Rural Dev 5(1&2), 70-78, June 2007